Step 1

Consider the system of equations:

y=2x+3

2x+4y=-8

Rearranging the system of equations:

2x-y=-3 ...(1)

2x+4y=-8 ...(2)

Step 2

Using elimination method

2x-y=-3 ...(1)

2x+4y=-8 ...(2)

\(\displaystyle\frac{{--+}}{{-{5}{y}={5}}}\)

\(\displaystyle{y}=\frac{{5}}{{-{{5}}}}\)

y=-1

put the value of y in equation (1)

2x-y=-3

2x-(-1)=-3

2x+1=-3

2x=-4

x=-2

Step 3

Result:

x=-2, y=-1

Consider the system of equations:

y=2x+3

2x+4y=-8

Rearranging the system of equations:

2x-y=-3 ...(1)

2x+4y=-8 ...(2)

Step 2

Using elimination method

2x-y=-3 ...(1)

2x+4y=-8 ...(2)

\(\displaystyle\frac{{--+}}{{-{5}{y}={5}}}\)

\(\displaystyle{y}=\frac{{5}}{{-{{5}}}}\)

y=-1

put the value of y in equation (1)

2x-y=-3

2x-(-1)=-3

2x+1=-3

2x=-4

x=-2

Step 3

Result:

x=-2, y=-1